Isocyanate toughening of pCBT/organoclay nanocomposites with exfoliated structure and enhanced mechanical properties - T. Abt; J. J. Bou; M. Sanchez-Soto (eXPRESS Polymer Letters)
Cyclic butylene terephthalate (CBT®) is an interesting matrix material for the preparation of nanocomposites due to its very low, water-like melt viscosity which favours clay exfoliation. Nevertheless, polymerized CBT (pCBT) is inherently brittle. This paper reports the preparation of isocyanate-toughened nanocomposites made from CBT and organo-modified montmorillonite. The role of the organoclay as reinforcement and the polymeric isocyanate (PMDI) as toughening agent on the properties of pCBT was studied. The organoclay increased the stiffness and strength by up to 20% whereas the PMDI improved the deformation behaviour. However, the PMDI did not affect the degree of clay dispersion or exfoliation and flocculated-intercalated structures were observed. The compatibility between the pCBT matrix and clay was further increased by preparing PMDI-tethered intercalated organoclay. The modified organoclay then exfoliated during ring-opening polymerization and yielded true pCBT/clay nanocomposites. This work demonstrates that reactive chain extension of CBT with a polyfunctional isocyanate is an effective method to obtain toughened pCBT nanocomposites. Moreover, isocyanates can enhance the compatibility between pCBT and nanofiller as well as the degree of exfoliation.